Procedural outcome following and Hemodynamic imaging analysis for anterior communicating artery wide-necked aneurysms by four different stents assisted coil embolization - Qiu, Yulong; Jiang, Li; Peng, Shixin; Zhu, Ji; Zhang, Xiaodong; Xu, Rui (Frontiers in Physics, 2023)
BACKGROUND: Anterior communicating artery (AcomA) aneurysm is the most common intracranial aneurysm (IA) and has the highest rupture rate. Previously, the preferred surgical treatment for intracranial aneurysms was microsurgery clipping (MC). With the gradual maturation of endovascular treatment (EVT), an increasing number of patients are inclined to treat IA with EVT. In recent years, an increasing number of scholars have suggested that the preferred treatment for wide-necked aneurysms is stent-assisted coiling (SAC). Currently, there are few studies on comparative analyses of the procedural results of SAC in AcomA aneurysms. METHODS: We retrospectively reviewed all consecutively treated patients who received SAC for AcomA aneurysms between February 12, 2013, and January 20, 2021. The primary procedural outcome was the occlusion rate evaluated with the Raymond–Roy occlusion classification (RROC) assessed on DSA at follow-up. Safety assessment included (1) ischemic complications (asymptomatic ischemia; intrastent thrombosis; coils falling off plug; arterial dissection); (2) bleeding complications (SAH; ICH); and (3) death. Univariate and multivariate logistic regression analyses were performed to determine patient baseline and aneurysm characteristics associated with total aneurysm occlusion at follow-up. Hemodynamic analysis was performed in one representative case each of the four stents, and six hemodynamic parameters were chosen,including wall shear stress (WSS), cavity blood flow velocity (CBFV), residual blood in the aneurysm (RBA),neck blood flow velocity (NBFV), blood flow inflow (BFI); and inflow concentration index (ICI). RESULTS: A total of 154 patients who underwent EVT via SAC were enrolled for comparative analysis of procedural outcomes. The median age was 55 years, and 56.49% (87) were female. At the first (6-10 months), second (12-15 months) and last (24-48 months) follow-up, complete aneurysm occlusion was observed in 94.8% , 94.8%and 94.2% of patients, respectively. There were no differences regarding the occlusion rates stratified by stent. Each stent showed a variable decrease in all hemodynamic parameters. CONCLUSIONS: Hemodynamic parameters all decreased significantly after SAC with all four different stents, and the effect of laser-cut stents on the hemodynamic decline of aneurysms appeared to be more significant than that of woven stents. No significant difference was observed in the follow-up RROC grade among the four stents.